(untitled) (Intent Research Scientific Journal, 2023)
Since beautiful teeth are important for self-esteem and a sense of comfort, there has been a trend in prosthetic dentistry towards the use of non-metallic restorative materials. Patients want their restorations to be aesthetically pleasing, biocompatible, natural-looking, and long-lasting.